2023
DOI: 10.1186/s13024-022-00591-3
|View full text |Cite
|
Sign up to set email alerts
|

FUS-ALS hiPSC-derived astrocytes impair human motor units through both gain-of-toxicity and loss-of-support mechanisms

Abstract: Background Astrocytes play a crucial, yet not fully elucidated role in the selective motor neuron pathology in amyotrophic lateral sclerosis (ALS). Among other responsibilities, astrocytes provide important neuronal homeostatic support, however this function is highly compromised in ALS. The establishment of fully human coculture systems can be used to further study the underlying mechanisms of the dysfunctional intercellular interplay, and has the potential to provide a platform for revealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 103 publications
(166 reference statements)
2
41
0
Order By: Relevance
“…In a second work, Dittlau et al implemented their model integrating iPSCsderived astrocytes and evaluating their role on hiPSC-derived MN network and NMJs functionality. [61] They demonstrated that astrocytes have a key role in ALS pathological mechanisms, being associated with destruction of MN network and interfering with NMJ formation and functionality through several gain-of-toxicity and loss-of-support processes. In a recent work, Fornetti et al tried to reproduce a reliable NMJ model in vitro able to investigate deficiencies in the neural and muscular cross-talk behind the junction formation in 𝛼-sarcoglycanopathy (𝛼-SG), a subtype of limb-girdle muscular dystrophy.…”
Section: D Microfluidic Platform For Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second work, Dittlau et al implemented their model integrating iPSCsderived astrocytes and evaluating their role on hiPSC-derived MN network and NMJs functionality. [61] They demonstrated that astrocytes have a key role in ALS pathological mechanisms, being associated with destruction of MN network and interfering with NMJ formation and functionality through several gain-of-toxicity and loss-of-support processes. In a recent work, Fornetti et al tried to reproduce a reliable NMJ model in vitro able to investigate deficiencies in the neural and muscular cross-talk behind the junction formation in 𝛼-sarcoglycanopathy (𝛼-SG), a subtype of limb-girdle muscular dystrophy.…”
Section: D Microfluidic Platform For Neurodegenerative Diseasesmentioning
confidence: 99%
“…implemented their model integrating iPSCs‐derived astrocytes and evaluating their role on hiPSC‐derived MN network and NMJs functionality. [ 61 ] They demonstrated that astrocytes have a key role in ALS pathological mechanisms, being associated with destruction of MN network and interfering with NMJ formation and functionality through several gain‐of‐toxicity and loss‐of‐support processes. In a recent work, Fornetti et al.…”
Section: Microfabrication Technologies For Organ‐on‐chip Platformsmentioning
confidence: 99%
“…Besides, ALS-susceptibility genes and LoF pathogenicity genes exhibited high strictness in astrocytes and oligodendrocytes, both these two cell types were shown to play important roles in ALS (Ferraiuolo et al, 2016;Stoklund Dittlau et al, 2023). Excitatory, inhibitory, cerebrospinal fluid contacting neurons also required strict expressions of ALS-susceptibility genes.…”
Section: The Strict Dosage Requirement Of Als-susceptibility Genes In...mentioning
confidence: 99%
“…Previous studies have shown increased reactive transformation in astrocytes harbouring mutations in different familial ALS genes, including SOD1, C9orf72, FUS, and valosincontaining protein (VCP) (Birger et al, 2019;Taha et al, 2022;Stoklund Dittlau et al, 2023).…”
Section: Sod1-mutated Astrocytes Undergo Reactive Transformationmentioning
confidence: 99%